2022
DOI: 10.1093/jee/toac090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cover Crop Planting and Termination Dates on Arthropod Activity in the Following Corn

Abstract: Relative to fallow-cash crop rotations, the addition of a cover crop can contribute to greater plant diversity and has the potential to conserve predatory arthropods. The transition of arthropods from a cover crop to a subsequent cash crop depends on several factors, such as cover crop biomass production and weather conditions. Information about the effect of cover crop planting and termination dates on arthropods in a subsequent corn system is limited. A two-year field study was conducted in Nebraska in 2018/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 74 publications
(82 reference statements)
1
13
0
Order By: Relevance
“…Pitfall traps were used to estimate the ground-dwelling arthropod activity with a focus on three sampling times that span the period of transition between the cover crop to corn. The pitfall trap design followed Carmona et al (2022) with one pitfall placed in the center of each split-plot. Arthropod activity during the transition from cover crop to corn was evaluated by placing pitfall traps at the early (hereafter: sample one) and late corn planting dates (hereafter: sample two) as well as at the first corn injury assessment (hereafter: sample three).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pitfall traps were used to estimate the ground-dwelling arthropod activity with a focus on three sampling times that span the period of transition between the cover crop to corn. The pitfall trap design followed Carmona et al (2022) with one pitfall placed in the center of each split-plot. Arthropod activity during the transition from cover crop to corn was evaluated by placing pitfall traps at the early (hereafter: sample one) and late corn planting dates (hereafter: sample two) as well as at the first corn injury assessment (hereafter: sample three).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Rosa et al (2021) performed field studies in western Nebraska, in a semi-arid environment, and reported that cover crops reduced maize grain yield regardless of the termination timing. Carmona et al (2022) also found decreased corn yields when cover crop biomass was increased. Even though having a decent cover crop biomass is frequently the goal for growers, any loss in the production of corn is likely a serious concern and potential impediment for growers when adopting cover crops.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations